KEPEMIMPINAN PEDAGOGI KEPALA SEKOLAH SEBAGAI UPAYA PENINGKATAN KUALITAS PENDIDIKAN DI ERA TRANSFORMASI DIGITAL DI SD IT DARUNNAJAH: STUDI KUALITATIF - Febriani Rahmatillah; Adi Asmara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The era of digital transformation urges a repositioning of the principal's role from a mere manager to a pedagogical leader who is adaptive to technology. This qualitative research, employing a library research method, aims to dissect the contribution of principals' pedagogical leadership in boosting the quality of digital education. Through content analysis of various scientific literatures, it was found that principals play a crucial role in formulating a digital vision, improving teachers' technological skills, triggering learning innovation, and optimizing IT-based academic supervision. However, its effectiveness is still overshadowed by infrastructure constraints, weak digital literacy among educators, and resistance to change. To overcome these obstacles, collaborative, adaptive leadership focused on continuous professional development is the main key.